Phylogenetic relationships among the Caribbean members of the Cliona Viridis complex (Porífera, Demospongiae, Hadromerida) using nuclear and mitochondrial DNA sequences (2010)
A species complex is a group of closely related species, where intraspecific variability overlaps with interspecific variation. Frequently, members of a species complex do not have complete reproductive isolation, therefore, the complex may go through extensive gene flow. In the Caribbean Sea, some encrusting and excavating sponges of the genus Cliona (Porifera, Hadromerida, Clionaide) are grouped within the great Cliona viridis complex because of its morphological similarities. This study examined the evolutionary relationships of the Caribbean members of the "Cliona viridis complex" (C. caribbaea, C. tenuis, C. aprica, and C. varians) and related taxa based on nuclear (ITSI and ITS2) and mitochondrial (3' end of ND6) sequences. The intragenomic ITS variation and its secondary structures were evaluated using a mixed approach of Denaturing Gradient Gel Electrophoresis (DGGE), DNA sequencing and secondary structure prediction. Considerable intragenomic variation was found in all the species, with apparently functional ITSI and ITS2 secondary structures. Despite the subtle morphological differentiation in these excavating sponges, the intragenomic copies of C. caribbaea, C. tenuis and C. aprica had a polyphyletic placement In the ITSI and ITS2 genealogies and very Iow divergence Therefore, it is clear that these species constitute a species complex (Ct-complex). "The only exception was C. varians, which presented a monophyletic clade and a group of putative specimens of Pione. These species were the closest Sister groups to the Ct-complex. Genetic distances revealed that part of the interspecific variation overlapped with intraespecific variation, which suggest either incomplete lineage sorting or extensive gene flow within the Ct-complex. Additionally our results support a monophyletic group with C. laticavicola and C. delitrix, but absence of reciprocal monophyly in the species, suggests their recent divergence. Our data shows that the 3' end of ND6, mitochondrial gene was highly conserved and not suitable for phylogenetic analysis at the interspecific level.